Factors Related to the Level of Health Literacy in Patients with Hypertension: Literature Review - Rezkisa Dwi Prambudia; Ika Yuni Widyawati; Eka Misbahatul Mar'ah Has (Universitas Airlangga, 2021)
Introduction: Hypertension is the leading cause of death worldwide. People with hypertension often receive health education about their health but cannot implement it. Patients with hypertension must be responsible for self-management related to the level of a person's health literacy, such as efforts that should they take so that the illness they suffer from is not getting worse. The aim of this study is to determine the factors related to the level of health literacy in hypertensive patients.Methods: Search for articles and journals conducted in the last ten years, from 2010-2020 and published on the internet using Scopus, Science Direct, ProQuest, Pubmed, Google Scholar, Portal Garuda, and SINTA by using chosen keyword adjusted to the Medical Subject Heading (MeSH) and Indonesian Thesaurus, namely,